Knowledge, Attitude, Practice and Perspectives Regarding Tobacco Cessation Program among Students in Private Dental Institution at Chennai –A Cross Sectional Study (Indian Journal of Public Health Research & Development, 2020)
Aim: Dentists could play an important role in tobacco cessation counseling. This study is conductedto assess dental professionals’ understanding of tobacco prevention and control methods. Material and Method: A descriptive cross sectional study was conducted in which a close-ended, self-administered 30item-questionnaire was distributed among 130 interns at private dental institutions in Chennai. Demographicdata, tobacco use status, attitudes toward cessation programs, perceived barriers and counseling procedurewas filled by the surveyed subjects. Results: About 97.7% of the dental interns agreed their role inhelping patients to quit smoking. Though 82.3% enquired all their patients regarding their smoking status,86.9% of them feared improper follow up. Nearly 85.4% of the respondents believed that the counselingdone is effective but only 32% anticipated successful intervention and 21% of them were very confident inconducting it. Conclusion: It was concluded that although dentists were aware of their obligations towardssmoking cessation counseling for patients but certain factors like lack of time, confidence, ,training,absence of reimbursement and fear of losing patients were the common barriers for the same. Expansion ofarmamentarium to include tobacco cessation counseling strategies in clinical practice must be adopted byall dental professionals.
Keywords: Tobacco, Smoking, Dentists, Counseling, Interns, Dental Institutions